Metode Penelitian Sanad - Ginting, Ernawati Beru (UIN Sumatera Utara Medan, 2024)
Based on the historical background of hadith, the object of hadith research is sanad or a series of hadith narrators. A narration cannot be said to be a hadith of the Prophet if it does not have sanad. The position of sanad is very important, Syuhudi Ismail in his book that Muhammad bin Sirin stated that indeed the knowledge of hadith is a religion, so pay attention to whom you take your religionThe research methods of sanad include: Definition of sanad, compilation of all the hadith paths studied, al-I''tibār, identification of narrators, iṭṭiṣāl, shaż and ''illat, and making conclusions. Furthermore, the practical steps of the hadith sanad research method can be applied into four parts: First, identify the narrator to know his justice and virtue. Second, Examining the connection of the sanad all information about the narrator must be collected, such as the biography of the narrator, when he was born and died, as well as the list of teachers, the list of students and the assessment of scholars about him. Third, syużūż and ''illat which function to find out irregularities Based on the results of the data collected, it can be concluded that the theory of tracing the sanad hadith can be applied to three. First, the sanad in question is a path or a series of narrators who convey the words of the Prophet Muhammad. Second, to collect all the sanad paths called takhrīj al-Ḥadīṡ. Third, al-I''tibār which functions to know mutabi'' and martyrdom. To make it clear that the processing of i''tibar activities is easy, it is necessary to make a scheme or the entire sanad of the hadith.